Peningkatan Kualitas Citra Termal Menggunakan Metode Blind Deconvolution - Mita Erlida Sipahutar; Sinar Sinurat; Imam Saputra (Forum Kerjasama Pendidikan Tinggi, 2021)
Temperature is a quantity that indicates the degree of heat of an object. The higher the temperature of an object, the hotter the object. Thermal imagery is an image created with thermal infrared spectrum that utilizes the temperature of an object. Sensing on this spectrum is based on differences in the temperature of the object and its emission power in the image which is reflected by the difference in hue or color. The sensor used in thermal images is noncamera based on scanning. In thermal imagery, there is a problem, namely blurred / blurred images that make it difficult to obtain information about objects. Blurred thermal images are caused by hot spots or rising temperatures. Thermal images often experience problems due to the large amount of diffraction fog in thermal imaging caused by the refractive index decreases as the wavelength increases. Blind deconvolution is a method that can be used to restore images that experience blur effects without having to know the value of the Point Spread Function (PSF). The process of improving the quality of thermal images is carried out using the blind deconvolution method which consists of 3 stages, namely finding the kernel value, looking for the convolution and estimation values ( ). Blind deconvolution method can be applied in improving the quality of thermal images by reducing the blur effect found in the image